Positifitas dan Ketercapaian Sistem Linier Fractional Waktu Kontinu - Fahcruddin, Imam (CAUCHY, 2011)
This paper studies a solution of the fractional continuous-time linier system. Necessary and sufficient condition were established for the internal and external positivity of fractional systems. Sufficient conditions are given for the reachability of fractional positive systems.